Desentralisasi dan Sumber Daya Aparatur: Problematika Pelaksanaan Desentralisasi Pelestarian Cagar Budaya di Provinsi Sumatera Barat, Riau, dan Kepulauan Riau - Sugiharta, Sri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2012)
This article discusses the implementation of the decentralization particularly in the field of cultural and heritage preservation. Through the elaboration of the case of cultural and heritage preservation in the province of West Sumatra, Riau and Riau Islands, this article argues that the core problem is related to the political will and the availability of personnel. This paper suggests that in order to ensure the preservation of cultural heritage, some organizational reform are needs to be taken followed by reform of the apparatus as a whole, both within the central and local government.